Pengembangan Aplikasi Text to Speech untuk Bahasa Bali - Mahendri Pramadewi, Pande Made; Windu Antara Kesiman, Made; Mahendra Darmawiguna, I Gede (Universitas Pendidikan Ganesha, 2013)
Text to Speech as an software that canconvert written text into spoken word will be veryuseful for people who have weak eyesight and peoplewho want to learn a spesific language, but exist Textto Speech software that has been developed by otherresearchers can not be applied for the Balineselanguage, where existance of Balinese language Textto Speech software is important as a culturalpreservation efforts in the midst of cultural extinctionissue in Indonesia. This research aimed to (1) design aBalinese language Text to Speech software; (2)implement the design of Balinese language Text toSpeech software. The research method used isdevelopment. The process of text-to-speechconversion, designed and implemented with two stageprocess: (1) the process of text-to-phonemesconversion; (2) the process of phonemes-to-speechconversion that uses diphone concatenation method byutilizing MBROLA and diphone database ID1generated by eSpeak. The results of this research is theBalinese language Text to Speech software that canconvert written text in latin letters of Balineselanguage to spoken words and also save the voices tooutput files such as audio file with *.wav extensionand MBROLA phoneme data file with *.phoextension. The software is named